CULTURAL IDENTITY IN YU HUA’S NOVEL TO LIVE - Hidayati Hidayati; Misla Geubrina; Mayasari Mayasari; Muhammad Kiki Wardana; zuindra zuindra (Universitas Islam Sumatera Utara, 2023)
Every ethnic group has its own cultural identity and is used as a reference to distinguish between one ethnic group and another. Understanding cultural identity is important to avoid cultural conflicts so that all ethnic groups within a unitary society can live side by side in harmony. The core discussion in this research is related to Chinese cultural identity based on the novel To Live written by Yu Hua with two points of discussion, kinship system and marriage system, conducted by means of a qualitative descriptive method to obtain data related to social phenomena with the results of the analysis in the form of description. Concepts and theories relating to cultural identity, Chinese cultural identity, kinship and marriage systems are implemented to support the overall research. The results of the analysis show that wherever Chinese ethnic groups are located, they try to maintain their cultural traditions. In Chinese culture, kinship includes all members of the extended family and the essence of a marriage is the union of two extended families; both have values that must be used as guidelines based on the teachings of Taoism, Confucianism and Buddhism; the value of maintaining and preserving harmonization and norms to bind each individual to remain in the corridor of cultural tradition heritage.